Advancing climate change adaptation in African food systems: Seven key priorities for action on adaptation - Campbell, Bruce M.; Sene, Amath; Attah, Alloysius; Ajayi, Oluyede; Fatunbi, Wole; Halloran, Afton; Jacobs-Mata, Inga; Kidane, Rahwa; Matsika, Ruwa; Nyambura, Mercy; Nyirongo, Jacob; Prager, Steve; et al. (2023)
Climate impacts in Sub-Saharan Africa are severe and will increase. Agriculture is a cornerstone of the economies of most countries and yet is dominated by climate-vulnerable rainfed systems. Meeting the food demands of the growing African population will require significant adjustments in food production systems and unfortunately, current adaptation efforts across the continent are insufficient to meet the climate challenge. This is demonstrated by lack of progress on National Adaptation Planning (NAP) processes, the likelihood of not achieving SDG2 on zero hunger, and the large numbers requiring humanitarian assistance because of climate change-related extreme events. Adaptation finance and funding are lacking, with international climate funding failing to reach the agreed targets and being dominated by indirect access. Private sector finance is limited but represents a massive opportunity. However, enabling policies and governance for adaptation need to improve. The following seven key priorities are discussed in this Discussion Starter: